2023
DOI: 10.3389/fimmu.2022.1098076
|View full text |Cite
|
Sign up to set email alerts
|

Using two-step cluster analysis to classify inpatients with primary biliary cholangitis based on autoantibodies: A real-world retrospective study of 537 patients in China

Abstract: BackgroundA variety of autoantibodies have been detected in primary biliary cholangitis (PBC), while the presence of autoantibody clusters and their clinical significance have not been fully understood. We aimed at defining autoantibody clusters and to better understand the clinical features and prognosis of PBC patients based on autoantibody clusters under real-world conditions.MethodsWe retrospectively analyzed 788 inpatients with PBC evaluated between October 2008 and July 2019, and included 537 patients. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The findings are in line with the conclusion of a recent study we conducted, which examined the clinical characteristics and prognosis of PBC patients using autoantibody clusters in real-world settings. Our study found that patients who tested positive only for AMA and/or AMAM2 had a higher incidence of NAFLD complications but a better overall disease prognosis than other PBC patients (42).…”
Section: Nafldmentioning
confidence: 44%
“…The findings are in line with the conclusion of a recent study we conducted, which examined the clinical characteristics and prognosis of PBC patients using autoantibody clusters in real-world settings. Our study found that patients who tested positive only for AMA and/or AMAM2 had a higher incidence of NAFLD complications but a better overall disease prognosis than other PBC patients (42).…”
Section: Nafldmentioning
confidence: 44%
“…The prognostic role of anti-gp210 antibodies has been recently confirmed in a large cohort study [66]. Therefore, the inclusion of anti-gp210 antibodies into the UK-PBC and GLOBE scoring systems could potentially enhance their risk stratification capabilities [67].…”
Section: Anamentioning
confidence: 93%